Sequencing of Circulating Microbial Cell-Free DNA Can Identify Pathogens in Periprosthetic Joint Infections. (15th September 2021) - Echeverria, Adriana P.; Cohn, Ian S.; Danko, David C.; Shanaj, Sara; Blair, Lily; Hollemon, Desiree; Carli, Alberto V.; Sculco, Peter K.; Ho, Carine; Meshulam-Simon, Galit; Mironenko, Christine; Ivashkiv, Lionel B.; et al.
Abstract : Background: Over 1 million Americans undergo joint replacement each year, and approximately 1 in 75 will incur a periprosthetic joint infection. Effective treatment necessitates pathogen identification, yet standard-of-care cultures fail to detect organisms in 10% to 20% of cases and require invasive sampling. We hypothesized that cell-free DNA (cfDNA) fragments from microorganisms in a periprosthetic joint infection can be found in the bloodstream and utilized to accurately identify pathogens via next-generation sequencing. Methods: In this prospective observational study performed at a musculoskeletal specialty hospital in the U.S., we enrolled 53 adults with validated hip or knee periprosthetic joint infections. Participants had peripheral blood drawn immediately prior to surgical treatment. Microbial cfDNA from plasma was sequenced and aligned to a genome database with >1, 000 microbial species. Intraoperative tissue and synovial fluid cultures were performed per the standard of care. The primary outcome was accuracy in organism identification with use of blood cfDNA sequencing, as measured by agreement with tissue-culture results. Results: Intraoperative and preoperative joint cultures identified an organism in 46 (87%) of 53 patients. Microbial cfDNA sequencing identified the joint pathogen in 35 cases, including 4 of 7 culture-negative cases (57%). Thus, as an adjunct to cultures, cfDNA sequencing increased pathogen detection from 87% to 94%. The median time to species identification for cases with genus-only culture results was 3 days less than standard-of-care methods. Circulating cfDNA sequencing in 14 cases detected additional microorganisms not grown in cultures. At postoperative encounters, cfDNA sequencing demonstrated no detection or reduced levels of the infectious pathogen. Conclusions: Microbial cfDNA from pathogens causing local periprosthetic joint infections can be detected in peripheral blood. These circulating biomarkers can be sequenced from noninvasive venipuncture, providing a novel source for joint pathogen identification. Further development as an adjunct to tissue cultures holds promise to increase the number of cases with accurate pathogen identification and improve time-to-speciation. This test may also offer a novel method to monitor infection clearance during the treatment period. Level of Evidence: Diagnostic Level II . See Instructions for Authors for a complete description of levels of evidence.